2019
DOI: 10.1177/2041419619860533
|View full text |Cite
|
Sign up to set email alerts
|

An optimization scheme for a multilayer armour module against 7.62 mm armour piercing projectile

Abstract: This study presents a methodology to find the optimal sequence and thicknesses of individual material layers in a multilayer armour module. The methodology is demonstrated with application to three different metal alloys: Armox-500T, Ti-6Al-4V and Al-2024. Numerical simulations are performed first to study the ballistic impact behaviour of these three materials using AUTODYN-3D code. The results of numerical simulations are compared with experimental results for validating the numerical models. Thereafter, a t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…The higher specific energy absorption of Al back layer results in higher ballistic resistance as compared to back Ti plate. The effect of using hard front layer effectively reduced the penetration capabilities of lead projectile whereas superior ductility of back Al plate converts the failure mechanism from localized shear defamation to global membrane stretching, hence promoting the energy absorption phenomenon in superior layer configuration (Paman et al, 2020).…”
Section: Ballistic Evaluationmentioning
confidence: 99%
See 1 more Smart Citation
“…The higher specific energy absorption of Al back layer results in higher ballistic resistance as compared to back Ti plate. The effect of using hard front layer effectively reduced the penetration capabilities of lead projectile whereas superior ductility of back Al plate converts the failure mechanism from localized shear defamation to global membrane stretching, hence promoting the energy absorption phenomenon in superior layer configuration (Paman et al, 2020).…”
Section: Ballistic Evaluationmentioning
confidence: 99%
“…The delamination of the multilayer metal-intermetallic target takes place due to the fracture of intermetallic layers in shock waves and the formation of main cracks in these layers. Paman et al (2020) performed ballistic tests on individual Armox-500T, Ti-6Al-4V and Al2024 target and multi-layer modules with different combinations of Armox-500T, Ti-6Al-4V and Al2024. It was observed that the combination Armox-500T/Ti-6Al-4V/Al2024 was found to be the best against 7.62 mm armour piercing projectiles.…”
Section: Introductionmentioning
confidence: 99%
“…Hrudayanjali Pathi, Tapan Kumar Mishri, et al  Layered composite material armor for helicopters has been developed with Titanium Alloy-Ceramics-Polymerbased lightweight composites which protect ammunitions to critical parts of the helicopters [77].…”
Section: Eejp 3 (2021)mentioning
confidence: 99%
“…Protection systems optimisations based on a numerical approach have successfully been performed by several authors. For example, Park et al [3] optimised thicknesses of a steel-aluminium two-layered armour impacted by a steel sphere based on finite element calculations; Paman et al [4] went further by numerically optimising a multi-layered armoured (steel, titanium, aluminium) based on layering order and layers thicknesses. However, these works are mostly limited to metallic materials or/and by initial assumptions, viz.…”
Section: Introductionmentioning
confidence: 99%